Utilizing Flaxseed as an Antimicrobial Alternative in Chickens: Integrative Review for Salmonella enterica and Eimeria - William C. Weston; Karen H. Hales; Dale B. Hales (Current Issues in Molecular Biology)
This review provides an integrative framework for understanding flaxseed (Linum utassitissimum) as an antimicrobial alternative for poultry production. We begin by familiarizing the reader with the global legislation of antibiotics in animal husbandry; highlighting gaps and current issues for Salmonella enterica (S. enterica) and Eimeria (coccidiosis-inducing). We then discuss the natural, symbiotic characteristics of the Galliformes order (chicken-like birds) and Linum (the flaxes). The key immunological themes in this review include: (i) flaxseed’s regulation of innate and adaptive immunity in chickens, (ii) flaxseed’s ability to accelerate chicken recovery from infection with S. enterica and Eimeria, and (iii) flaxseed’s strengthening of immunity via vitamin B6 antagonism. Research indicates that whole flaxseed increases adaptive immune capacity by augmenting cecal Bacteroides and short-chain fatty acids while also attenuating the heterophil to lymphocyte ratio in chickens. Moreover, flaxseed accelerates chicken recovery from infection with Salmonella Enteritidis or Eimeria tenella; however, future work is needed to better understand (i) defatted flaxseed’s superior performance against Eimeria species and (ii) Eimeria maxima’s resilience against whole flaxseed. In the context of vitamin B6 antagonism, we propose that 15% whole flaxseed overcomes S. enterica’s insult to estrogen synthesis by sustaining the activity of phosphatidylethanolamine methyltransferase (PEMT) in liver. We also propose that 10% defatted flaxseed (as a metformin homologue) strengthens chicken immunity by safeguarding gonadal physiology and by increasing plasma thymidine bioavailability. The concepts in this review can be used as a template for conducting advanced immunological studies in poultry science.